Tailored heat treated accumulative roll bonded aluminum blanks: failure under bending stresses - Nguyen, H.; Boehm, W.; Tsoupis, Ioannis; Göken, Mathias; Höppel, Heinz Werner; Schmidt, Christian; Hausöl, Tina; Ruppert, Mathis; Merklein, Marion (Production Engineering, 2016)
Ultrafine-grained accumulative roll bonded (ARB) sheet metals of aluminum alloys have a high potential for lightweight construction. The mechanical properties can be enhanced regarding strength and ductility by the combination of ARB and a local heat treatment according to the Tailor Heat Treated Blanks technology. The present investigation focuses on the failure behavior of ultrafine-grained ARB blanks. Due to the low formability of these high-strength ARB metals, a detailed understanding of the failure mechanisms is essential. For this purpose, an established approach to determine the different stages of damage of the material for conventional materials is now applied to multilayered aluminum in the as-received and heat-treated condition. In this context, air bending tests are used to qualify and quantify the bending and forming behavior of ARB sheets of AA1050A and AA6016 aluminum alloys.
Keywords: Tailor Heat Treated Blanks (THTB); Ultrafine-grained microstructure (UFG); Failure; Formability; Bending; Accumulative roll bonding (ARB)